1998
DOI: 10.1097/00002060-199811000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Atrophy of Suboccipital Muscles After a Cervical Injury

Abstract: This case report describes abnormalities in bilateral rectus capitis posterior minor muscles in one individual with persistent head and neck pain. These findings are muscle atrophy, fatty infiltration on magnetic resonance imaging, and electromyographic abnormalities compatible with denervated muscle. The objective of the study contained herein was to determine if fatty infiltration on magnetic resonance imaging of the rectus capitis posterior minor muscle is the result of disuse or denervation. Electromyograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 15 publications
0
26
0
1
Order By: Relevance
“…The mean CSA of the trunk at rest was 393.90 6 8.07 cm 2 , which decreased to 362.61 6 8.85 cm during the ADIM. 2,39 There was a corresponding significant increase in thickness of the TrA and OI muscles during the ADIM, as measured by both MRI and USI. The activation was symmetrical between sides.…”
Section: 91mentioning
confidence: 81%
See 1 more Smart Citation
“…The mean CSA of the trunk at rest was 393.90 6 8.07 cm 2 , which decreased to 362.61 6 8.85 cm during the ADIM. 2,39 There was a corresponding significant increase in thickness of the TrA and OI muscles during the ADIM, as measured by both MRI and USI. The activation was symmetrical between sides.…”
Section: 91mentioning
confidence: 81%
“…2,11,12,109 Although magnetic resonance imaging (MRI) is considered the gold standard for detecting these changes, researchers have suggested that USI may also provide some insight, as these tissue changes result in a degeneration of a muscle's architectural features and an increase in their echogenicity. 55,100 In a prospective study, Strobel et al 100 developed a qualitative evaluation tool ( TaBle 1) to evaluate the accuracy of USI in depicting fatty atrophy of the supraspinatus and infraspinatus muscles, using MRI as the reference criterion.…”
Section: Tissue Compositionmentioning
confidence: 99%
“…Clinically, alterations of the suboccipital muscles can lead to compression of neural elements (Andary et al, 1998) and the role that RCPm muscle plays a role in head posture at cervical level and could be linked to cervicogenic headache, in some cases associated with muscle attachments to the dura mater (Nayak et al;Hallgren et al, 2014b;Farmer et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…However, on the contrary, higher muscle fat indices in the subjects with chronic WAD were present in the suboccipital muscles and the deep segmental multifidii, which may point to more specific pathophysiological processes. Two other studies have provided preliminary evidence of an association between sub-occipital muscle degeneration and persistent pain [1] and balance disturbance [37]. A higher incidence of dizziness and unsteadiness has been reported by patients with chronic WAD, suggesting that such disturbances were the result of altered somatosensory input [61].…”
Section: Introductionmentioning
confidence: 98%